Islamic Educational Epistemology in the Algorithmic Era: A Critical Discourse Analysis of Religious Authority on Digital Social Media - Mohammad Zaki; Murdan Murdan; Samsul Fahmi; Rizwan Hakiki; Lalu Tata Gresa Wangsa; Budi Hartawan; Lalu Ahmad Kholis` Bukran; Khaeruman Al Kaelani (Perkumpulan Dosen Tarbiyah Islam, Indonesia, 2026)
This study examines Islamic educational epistemology in the algorithmic era, focusing on how religious authority is shaped through digital social media. Using Critical Discourse Analysis (CDA), the research analyzes religious content on TikTok, Instagram, and YouTube to explore how algorithm-driven platforms influence the production and legitimization of Islamic knowledge. Using a qualitative approach, data were collected from videos, captions, hashtags, and audience interactions. The findings show that algorithmic systems tend to prioritize short, emotionally engaging, and highly interactive religious content over academically grounded explanations. As a result, religious authority is increasingly determined by digital visibility, such as followers, likes, and virality, rather than traditional scholarly credibility. The study also found that complex Islamic concepts are often simplified into motivational and performative narratives to suit platform algorithms and audience preferences. These findings indicate that digital media not only expands access to Islamic learning but also reshapes the epistemological foundation of Islamic education. Therefore, this study highlights the importance of integrating critical digital literacy into Islamic education curricula to help students critically evaluate online religious content and distinguish between algorithmic popularity and scholarly authority.